From the Failure of Desegregation to the Failure of Choice - Wendy Parker (Washington University Journal of Law & Policy, 2012)
As we commemorate the fortieth anniversary of the St. Louis school desegregation litigation, a natural question is how current education reform efforts impact the status of and potential for school integration. This Article examines how the push for school choice impacts school desegregation in Missouri specifically and the United States generally. The evidence reveals that while our student population is becoming more diverse and the prevalence of all-white schools is diminishing, the pattern of high-poverty, high-minority, low-performing schools persists. Charter schools—the most common form of school choice—actually exacerbate the segregation of poor and minority school children. As a first step in rectifying the segregative impact of charter schools, this Article proposes that the federal government require more inclusionary practices by charter schools for states to receive federal funding for their charter schools. Otherwise, we once again allow current reform efforts to continue our history of segregated, unequal schooling.
Keywords: school desegregation; st. louis school desegregation litigation; education reform; school choice; charter schools; Brown v. Board of Education; Liddell; missouri school segregation; statutory integration